Sustainable Competences in Higher Educa-tion – Pre-pilot Study - Ruge, Dorte; Dawn Johannsen, Heather; Thedchanamoorthy, Thujetha; Rousing Lauridsen, Anja; Mikkelsen, Stinus; Gaarsmand, Solveig (Futures of Education, Culture and Nature - Learning to Become, 2024)
This paper presents results from a case study of a Pre-pilot educational activity in the Erasmus+ project on Sustainable Competences in Higher Education Institutions (2022-2024). Teacher students’ acquisition of sustainable competences represents a major educational challenge at bachelor level and generally in education in Nordic countries and internationally. With reference to UNESCO guidelines, the overview of results indicated that in the cognitive domain learning outcomes in a medium to a high degree included acquisition of natural science knowledge about sand mining and sustainability. Furthermore, the interdisciplinary teaching methods seemed to a medium degree to facilitate teacher student motivation and learning outcomes in relation to socio-emotional dimensions and interculturality. In the behavioral domain, results indicated that student teachers to a high degree acquired competences to imagine realistic scenarios within an educational context. More research is needed in student-centered approaches, and we hope that the project has contributed to the current need for bridging the gap between traditional education and more student-centered learning in relation to ‘Futures of Education.’